Transitioning to a Progressive Green Economy in the Philippines. Issue 2 (June 2020) - San Juan, David Michael M.
Informed by theoretical discussions and statistics on the Anthropocene and sustainable development, this article is focused on tackling Sustainable Development Goals (SDGs), primarily SDG 1 ("end poverty in all its forms everywhere"); SDG 7 ("ensure access to affordable, reliable, sustainable and modern energy for all"); SDG 10 ("reduce inequality within and among countries"); and related SDGs that are at the nexus of poverty, inequality, and renewable energy. This discussion serves as a springboard for (re)crafting a state-led sustainable development plan for the progressive transition to a green economy in the Philippines, as a pro-active response to global environmental change.